Rapid presumptive identification of enteropathogenic Escherichia coli in faecal smears by means of fluorescent antibody: 3. Field evaluation - Cherry, William B. (1961)
This paper reports on the evaluation of the fluorescent antibody technique for detection of enteropathogenic Escherichia coli in faecal smears from children both with and without diarrhoea. In field studies involving 315 children in Puerto Rico, it was demonstrated that presumptive diagnosis of infection with enteropathogenic E. coli could be made more rapidly and with greater sensitivity by immunofluorescence than by isolation and slide agglutination. The specificity of the fluorescent antibody test was of the same order as that of slide agglutination tests with OB antisera. The incidence of salmonellae, shigellae, coagulasepositive staphylococci and Candida in the diarrhoeal specimens was studied, but no relationship appeared to exist between these organisms and the enteropathogenic E. coli. Although several publications dealing with the detection of enteropathogenic E. coli by fluorescent antibody techniques have appeared previously, this is the first report on a field evaluation based on definitive serotyping of all strains isolated. Complete identification is essential to a true evaluation of immunofluorescence as a tool for rapid detection of enteropathogenic E. coli in faecal smears. The value of fluorescent antibody techniques for the presumptive diagnosis of infantile diarrhoea caused by E. coli and for monitoring institutional populations has been confirmed by these studies.